2009
DOI: 10.1159/000230026
|View full text |Cite
|
Sign up to set email alerts
|

Inversion, Hydration and Diuresis during Extracorporeal Shock Wave Lithotripsy: Does It Improve the Stone-Free Rate for Lower Pole Stone Clearance?

Abstract: Objective: It was the aim of this study to assess the efficacy and safety of combined forced hydration and diuresis with limited inversion during shock wave lithotripsy (SWL) by comparing this treatment modality with conventional SWL for lower calyceal nephrolithiasis. Patients and Methods: In this prospective, non-randomized study, we included 100 patients with lower calyceal calculi ≤2 cm. Fifty of them received conventional SWL and the other 50 underwent SWL combined with oral hydration, diuresis and 12° in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 30 publications
0
23
0
3
Order By: Relevance
“…The altered position of the kidneys is often combined with vibration on the body surface to add some kinetic energy. This treatment approach can be used in patients with residual fragments in the lower pole of the kidneys 266269 , although the results have been conflicting 270 .…”
Section: Discussionmentioning
confidence: 99%
“…The altered position of the kidneys is often combined with vibration on the body surface to add some kinetic energy. This treatment approach can be used in patients with residual fragments in the lower pole of the kidneys 266269 , although the results have been conflicting 270 .…”
Section: Discussionmentioning
confidence: 99%
“…Diuretics will increase urine flow and thus the probability of cavitation [19,20]; which means, pieces of the broken stone shell increase, and the centre of the stone is exposed to subsequent shockwaves allowing entry of urine through the broken surface, thus giving an adequate interface with the centre of the stone [15]. The size of the stone is an important prognostic factor for successful ESWL and is considered as a highly effective treatment option for lower pole stones ≤2 cm [21].…”
Section: Discussionmentioning
confidence: 99%
“…Followup at 3 months showed that 83.3% of the patients belonging to the study group were rendered stone-free, whereas 71.5% were stone-free in the control group, without statically significant difference [45]. …”
Section: Management Of Residual Stonesmentioning
confidence: 99%